Structure and Performance of Advisory Services in Agricultural Development around Protected Area: The Case of Xuan Thuy National Park, Vietnam - Nhung , Nguyen Thi Trang; Cuong, Tran Huu; Lebailly , Philippe (Asian Journal of Agriculture and Rural Development, 2020)
The study was conducted in the buffer zone of Xuan Thuy National Park (XTNP), the largest wetland ecosystem in Northern Vietnam, to assess the governance structure and performance of agricultural advisory services (AAS) in agricultural production under the context of environmental protection. Based on a sample of 12 officials from diverse organizations and 234 farmers living nearby the park, the results revealed that agricultural production received supports from both public and private sectors, including communal agricultural board (CAB), communal agricultural cooperative (CAC), XTNP management board, irrigation companies, and input dealers. There were huge differences in advisory flows, methods, and effectiveness according to types of AAS providers and production systems. Rice production received more technology transferred from CAC, CAB and irrigation companies as compared to aquaculture farming. Meanwhile, aquaculture sectors obtained more consultation from input dealers. Among public sectors, XTNP’s managers were partly responsible for raising awareness of environmental protection of the inhabitants but this organization has a small role in the agricultural development of peripheral communities.